Offense and defense statistical indicators that determine the Greek Superleague teams placement on the table 2011 - 12 - Bekris, E.; Mylonis, E.; Sarakinos, A.; Gissis, I.; Gioldasis, A.; Sotiropoulos, A. (Journal of Physical Education and Sport, 2013)
The aim of the present study was to determine the differences in offense and defense performance indicators which influence the final placement on the table of the Greek Superleague. The sample comprised 240 matches of the Greek Superleague in the 2011 - 12 season. The teams were categorized based on their final placement on the table. The four categories that were compared were: G1, the Champion team, G2, the teams that earned the right to participate in the play offs, G3, the teams that simply remained in the Superleague, and G4, the teams that were demoted. There was variance analysis by one-way anova, and the comparisons among categories (Post hoc Bonferoni) were conducted in significance level a=0.1. The results showed that the Champion team (G1) surpassed its immediate competitors (G2) in offense performance indicators, namely goals scored (p = 0.000), number of assists (p = 0.000), total number of shots (p = 0.000), crosses (p = 0.000), number of assists (p = 0.000), and number of assists and goal per game (p = 0.000), as well as in defence performance indicators, that is total shots against (p= 0.004) , shots against inside the 16m (p=0.020) , shots against outside the 16m (p= 0.032), number of crosses against (p=0.005), passing effectiveness against (p=0.049). High level teams (G1&G2), which ranked 1st - 5th, showed common quality differences in offense and defense performance indicators in comparison to those that ranked 6th - 16th (G3&G4). Those indicators were the effectiveness of passes and shots on goal, and the lower accuracy of the opponents` passes. The present study also shows that the final placement on the table is further influenced by different quantity and quality offense and defense performance indicators depending on the levels of the compared teams.